Pengujian Peraturan Pemerintah Terhadap Kelayakan Penerima Bantuan Siswa Miskin Menggunakan Algoritma TOPSIS - muhammad safii; Surya Ningsih (LPPM Politeknik LP3I Medan, 2018)
ABSTRACT The BSM Program is a National Program aimed at eliminating the barriers of poor students participating to school by helping poor students gain access to appropriate education services, prevent dropping out, attract poor students to return to school, help students meet needs in learning activities, support the Compulsory Education Program Basic Nine Years (even to the upper secondary level), as well as helping the smoothness of school programs. Through the BSM Program it is expected that school-aged children from poor households / families can continue to go to school, not dropping out of school, and in the future it is hoped that they can break the poverty chain that their parents are currently experiencing. The BSM program also supports the government's commitment to increase education participation rates in poor and remote districts / municipalities as well as to marginalized groups. This program is a direct aid to students and not a scholarship, because based on students' economic conditions and not on merit (scholarship) considering the condition of the students, while scholarships are given taking into account student achievement. In this research used support system with Technique for Order Performance method by Similarity to Ideal Solution or TOPSIS. This method is known as the weighted summing method. The basic concept of the TOPSIS method seeks a weighted sum of performance ratings on each alternative on all attributes. The TOPSIS method requires the process of normalizing the decision matrix (X) to a scale comparable to all the alternatives available so as to produce a ranking. Keywords: Decision Support System, BSM, Ranking, TOPSIS